Labor reforms, macroeconomic imbalances and unployment in Colombia (1999)
In the first half of the nineties, Colombian labor legislation faced profound transformations. Initially, the reforms seemed to produce positive effects as unemployment fell continuously, to below 8% in 1994. However, since 1995, unemployment has increased steadily, reaching in the last quarters the highest levels ever recorded: almost 20%. The latter is explained by two types of factors. First, lower GDP growth, generated by growing macroeconomic imbalances -such as fiscal and current account deficits-, and social disorder and institutional disarray. Second, the persistence of a number of structural factors affecting the labor market: higher relative price of labor with respect to capital, real exchange rate appreciation, increase in the wage differential, increase of payroll taxes, rising participation rates particularly for females and the historically high level of the "natural" rate of unemployment. Therefore, a strategy to create new working posts and reduce the extremely high unemployment rates should combine policies aiming at enhacing growth controlling the fiscal deficit and restructuring the composition of expenditure in favor of investment and at dampening the causes that tend to maintain the mismatch between supply and demand in the labor market. Efforts should also be made in order to further flexibilise the labor market.